The Impact of Social Ties in enhacment of Islamic Brotherhood in the Era of Prophecy - Mustafa, Ali Salih Ali (Journal of Islamic and Religious Studies, 2018)
This research addresses Islam's view of the social ties that man creates by virtue of his living among the people or in which he borns as its member, and aims to answer several questions about the relationship of these social ties with the Islamic brotherhood bond that Islam has brought. Does Islam recognize the social ties? On which basis does Islam recognize them and why? What is their position in front of Islamic brotherhood? How does Islam invest these ties to achieve religious, psychological and social security? Are there any conditions that Islam has developed to recognize and nurture these ties? The answer to these questions comes through the Qur’ānic texts, the prophetic Hadiths and the events of the Prophet's biography, based on open and direct reference, and away from the ambiguous interpretations or weak evidences; in order to clarify this matter clearly, and to check the validity of the results of the study.